تحليل مؤشرات النقل البحري الدولي للبضائع دراسة حالة لمجموعة من الدول العربية في الفترة (2010-2023) - عبد الفتاح بن يامه; محمد بقاص; محمد البشير بن موسى (جامعة الوادي University of Eloued, 2025)
"تحتوي الدراسة على فصلين، حيث تناولت في فصلها النظري المفاهيم الأساسية المتعلقة بالنقل البحري، أهميته، أنواعه، ومؤشرات قياس أدائه، في حين خصص الفصل التطبيقي لتحليل البيانات والمؤشرات الخاصة بالتجارة البحرية ومعايير الأداء اللوجستي ومؤشرات الموانئ في الدول المعنية. أظهرت النتائج أن معظم الدول العربية لا تزال تواجه تحديات كبيرة في مجال النقل البحري، منها ضعف البنية التحتية، وقصور في الأنظمة الإدارية والرقمية، إلى جانب ضعف التكامل بين الموانئ العربية. كما تبين من خلال مؤشر الأداء اللوجستي أن غالبية الدول العربية تسجل مستويات متوسطة إلى ضعيفة مقارنةً بالدول المتقدمة، ما يؤثر سلبًا على قدرتها التنافسية في سلاسل الإمداد العالمية. وقد أظهرت الدراسة تباينًا واضحًا بين الدول من حيث تطور موانئها واستثماراتها في القطاع، حيث برزت دول الخليج العربي (مثل الإمارات والسعودية) كنماذج متقدمة نسبيًا مقارنة بدول شمال إفريقيا والمشرق العربي. وفي المقابل، سجلت بعض الدول تحسنًا طفيفًا في السنوات الأخيرة نتيجة الإصلاحات الجزئية والتوجه نحو الرقمنة. "The study contains two chapters, where in its theoretical chapter, the basic concepts related to maritime transport, its importance, types, and indicators of its performance measurement, were dedicated, while the applied chapter is devoted to analysis of data and indicators of marine trade, logistical performance standards and ports indicators in the countries concerned. The results showed that most Arab countries are still facing great challenges in the field of maritime transport, including weak infrastructure, and palaces in administrative and digital systems, as well as poor integration between Arab ports. It was also found through the logistical performance index that the majority of Arab countries record medium to weak levels compared to developed countries, which negatively affects their competitiveness in global supply chains. The study showed a clear variation between countries in terms of the development of their ports and investments in the sector, as the Arab Gulf states (such as the Emirates and Saudi Arabia) emerged as relatively advanced models compared to North African countries and the Arab East. On the other hand, some countries have registered a slight improvement in recent years as a result of partial reforms and the trend towards digitization.
ماستر
Keywords: النقل البحري الدولي; البضائع، المؤشرات; International maritime transport; freight; indicators.